2021
DOI: 10.1186/s12885-021-08062-6
|View full text |Cite
|
Sign up to set email alerts
|

High vimentin expression with E-cadherin expression loss predicts a poor prognosis after resection of grade 1 and 2 pancreatic neuroendocrine tumors

Abstract: Background Pancreatic neuroendocrine tumors (pNETs) are a heterogeneous group of neoplasms with malignant behaviors that can develop from inert slow growth or low malignancy to aggressive metastasis during follow-up. Recently, vimentin and E-cadherin were shown to be prognostic markers in some malignant tumors but were not evaluated in pNETs. The aim of this study was to evaluate the expression and prognostic significance of vimentin and E-cadherin in grade 1 and 2 pNETs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Finally, not only does PKD1 signaling promote metastatic potential by upregulating expression of vimentin and increasing the number of ALDH1 + CSCs [ 87 , 88 , 89 ], this pathway may also increase the expression of CD36 to activate fatty acid metabolism and further enhance metastatic potential [ 62 ]. Therefore, identification of the PKD1 pathway in CSC plasticity with a partial EMT phenotype may provide new insights into CSC biology in a variety of cancer types, since EMT is important during the metastatic stage, while E-cadherin-induced MET facilitates subsequent colonization [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, not only does PKD1 signaling promote metastatic potential by upregulating expression of vimentin and increasing the number of ALDH1 + CSCs [ 87 , 88 , 89 ], this pathway may also increase the expression of CD36 to activate fatty acid metabolism and further enhance metastatic potential [ 62 ]. Therefore, identification of the PKD1 pathway in CSC plasticity with a partial EMT phenotype may provide new insights into CSC biology in a variety of cancer types, since EMT is important during the metastatic stage, while E-cadherin-induced MET facilitates subsequent colonization [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, not only does PKD-1 signaling promote metastatic potential by upregulating expression of vimentin and increasing the number of ALDH1 + CSCs [81][82][83], this signaling also increases the expression of CD36 to activate fatty acid metabolism and further enhances metastatic potential [57]. Therefore, identification of the PKD-1 pathway in CSC plasticity with a partial EMT phenotype may provide new insight into CSC biology in a variety of cancer types since EMT is important during the metastatic stage while E-cadherin-induced MET will aid in the subsequent colonization [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Less is known about vimentin in NENs. In a study of patients with Grade 1 and 2 NENs, approximately 25% tumour tissues expressed vimentin [ 40 ]. Our data showed that three out of the four G3 tumours had lower vimentin relative to that in non-tumour than the G2 tissue did.…”
Section: Discussionmentioning
confidence: 99%